Development of Learning Media For Vector Suvject Matter - Tyas, Hartining; Suttiwan, Witsanu (Program Magister Teknologi Pendidikan Universitas Jambi, 2023)
This research focuses on the development of learning media to teach vector concepts to improve students' understanding of vector addition, vector projection, and dot product calculations. This research uses a Research and Development (R&D) approach, which involves media design using Corel Draw and CNC technology for acrylic material fabrication. Validation was conducted by subject matter experts and media specialists to ensure the accuracy and interactivity of the content, while field trials tested the effectiveness of the media with high school students. The results showed that the learning media achieved an accuracy level of 0.17% in the parallelogram method, 0.60% in component analysis, and 0.83% in dot product projection, indicating high precision in visualizing the magnitude and direction of vectors. Validation feedback rated the content, conceptual alignment, design, and interactivity as good to excellent, with an average score of 80-92%. Therefore, this learning tool is considered effective and useful in helping students overcome difficulties in mastering vector concepts.